Características Epidemiológicas Frecuentes En Conductores Lesionados Por Accidentes De Tránsito, Cubiertos Por El Soat, Atendidos En El Hospital Regional Docente De Trujillo, Durante El Periodo 2006 - 2011. - Mariñes López, Demetrio David (2012)
Objective: determine the epidemiology , drivers injured in traffic accidents in the HRDT. Material and Methods: descriptive study. The sample population consisted of 351 drivers injured in traffic accidents , covered by SOAT, which were treated at the Regional Hospital of Trujillo, during the period 2006-2011, who were analyzed according to their epidemiological characteristics. Results: features that had higher fatality rate were: 2008, males, those over 60 years, holding no driving license, at dawn, on Mondays and Saturdays, roads, rollover, motorcycle ar buses and diagnosis of cervical trauma. Frequencies of fatally injured drivers are higher than those with nonfatal injuries regarding tenure no driving license, be injured in the morning, be injured in highway, be injured by such rollover accident and the diagnosis of multiple lesions (p <0.05). Conclusion: the frequency distribution of injured drivers are dífferent ,just as there were significant differences between drivers with non-fatal injuries.